Optimization of Fiber Digestibility and Methane Reduction with Gambier Leaf Extract from Pangkalan for Sustainable Ruminant Farming - Pazla, Roni; Natsir, Asmuddin; Hidayat, Rahmad; Ginting, Nurzainah; Zain, Mardiati; Antonius; Mohd-Aris, Aslizah; Ikhlas, Zaitul; Hidayat, M. Zhorif (Andalasian Livestock, 2024)
Ruminant livestock production plays an important role in providing animal protein sources, but faces major challenges in terms of feed utilization efficiency and environmental impact due to methane emissions. Methane produced by rumen fermentation not only contributes nearly 30% of global greenhouse gas emissions but also causes energy losses of 7-12% of total feed energy. This study aimed to evaluate the effect of gambier (Uncaria gambier) leaf extract from Pangkalan, West Sumatra, on the digestibility of fiber fractions (NDF, ADF, cellulose, hemicellulose) and methane gas production in ruminant rations. The study was conducted in vitro using the method of Tilley and Terry (1963) with a randomized group design consisting of four treatments: T0 (control without gambier extract), T1 (0.5% gambier extract), T2 (1% gambier extract), and T3 (2% gambier extract), with four replications using goat rumen fluid. Results showed that the addition of gambier extract significantly increased NDF and ADF digestibility to 64.30% and 63.77% at T3, respectively, compared to the control of 61.67% and 61.56%. Cellulose digestibility increased from 64.57% at T0 to 67.20% at T3, while hemicellulose increased from 64.78% to 67.44%. In addition, methane gas production decreased significantly from 22.45 ml/g DOM in the control to 16.67 ml/g DOM in T3, equivalent to a decrease of 25.74%. The optimal dose to increase fiber digestibility and decrease methane production was 2% gambier leaf extract (T3 treatment). Thus, gambier leaf extract from Pangkalan can be used as an effective natural feed additive to improve feed efficiency while reducing the environmental impact of ruminant farming.